Land Capability in Gobeh Sub Watershed Wonogiry Regency Central Java Province - Taryono, Taryono (Forum Geografi, 1999)
The research held on Sub DAS of Gobeh, Wonogiri Regency, have the aims to kno about class and sub-class of land capability in the research area. The other aim is to know about some area developed to the farming land, and to evaluate about land apability currently. The method used in this research is field-survey method, including about observation, measurenment, reording, and laboratory analysis. The sampling method applied in this research is stratified sampling, with land unit stratum. Measurenment and recording in the field inluding about degree of slope, erosion level, soil-deepening, drainage, stone or gravel and flood hazard. The laboratory analysis including about land erodibility, texture, and permeability. The research result identify that, researh fields have three lanf form unit, they are the fluvio volanic foot plain of old Lawu vulcan area flat relief slightly dissected, the fluvio volcanic foot plain of old Lawu mountain area rolling relief medium dissected, and flat foot plain unit can be separated to thirty two land unit. Land capability of the research field identify between level II to level VII. The wide of each land capability are, level II 3 â 8 Ha (2,4%), level III 38,18 Ha (23,7%), level IV 10 Ha (6,33%), level V 107,62 Ha (66,8%), level VII 1,2 Ha (0,75%).